Death and disease in the ancient city - Hope, Valerie M., 1968-; Marshall, Eireann, 1967- (Routledge classical monographs., 2000)
Human frailty and mortality influence the structure and functioning of all societies; questions of how the ancients coped with their own mortality, how they sought to classify and control the causes of death, and how they treated the dying and the dead, are therefore central to any understanding of antiquity. This innovative volume draws upon recent research in archaeology, ancient history, and the history of medicine to evaluate all these issues. It addresses a wide range of topics, including views of ancient disease causation; public and private health measures; how the natural and urban environment affected the well-being of the individual; how the city was organised to protect the health and safety of the living; and how the living sought protection from the polluting influence of both the diseased and the dead. Lucid and accessible, this work is the first to unite the study of death and disease in antiquity, providing valuable insights into how these factors shaped the ancient city. It will appeal not only to classical scholars and students, but to all those interested in the history of death and disease.